2019
DOI: 10.3390/diagnostics9010033
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pulmonary Function Testing from Quantified Computed Tomography Using Machine Learning Algorithms in Patients with COPD

Abstract: Introduction: Quantitative computed tomography (qCT) is an emergent technique for diagnostics and research in patients with chronic obstructive pulmonary disease (COPD). qCT parameters demonstrate a correlation with pulmonary function tests and symptoms. However, qCT only provides anatomical, not functional, information. We evaluated five distinct, partial-machine learning-based mathematical models to predict lung function parameters from qCT values in comparison with pulmonary function tests. Methods: 75 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…The substantial difference in the relative volume of residual normal lung density among the three groups, indicating the value is associated with the severity of illness and thus prognosis. The similar LAV values of the three COVID-19 pneumonia groups to the normal CT groups indicated that no obvious sign of emphysema observed in pneumonia at the initial CT scan, as the setting of the LAV threshold for emphysema was -950 HU 30 . The HAV values increased in more severe cases, indicating an increase in high-density lesions and providing evidence that the total score for crazy-paving and consolidation could be as a qualitative indicator for evaluating disease progression.…”
Section: A C C E P T E Dmentioning
confidence: 71%
See 1 more Smart Citation
“…The substantial difference in the relative volume of residual normal lung density among the three groups, indicating the value is associated with the severity of illness and thus prognosis. The similar LAV values of the three COVID-19 pneumonia groups to the normal CT groups indicated that no obvious sign of emphysema observed in pneumonia at the initial CT scan, as the setting of the LAV threshold for emphysema was -950 HU 30 . The HAV values increased in more severe cases, indicating an increase in high-density lesions and providing evidence that the total score for crazy-paving and consolidation could be as a qualitative indicator for evaluating disease progression.…”
Section: A C C E P T E Dmentioning
confidence: 71%
“…The evaluation index method was displayed by quantifying the percentage of the voxel below the low attenuation value (LAV) (threshold of -950HU) and above the high attenuation value (HAV) (threshold of -200 HU). The FWHM parameter marks the width of frequency distribution at half of the maximum CT value, representing the heterogeneity of lung tissue density 30 .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Among quantitative CT methods, those related to thoracic imaging are the most studied [20,22,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. In particular, the applications related to the classification and management of lung nodules are the most well-known and are used in both clinical practice and lung cancer screening programs [20,22,23,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the quantitative analysis of medical CT images are constantly expanding, and the applications of such methods in the thoracic field are increasing [4,5,9,14,[17][18][19][20][21][22]28,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%